Finite element analysis of box girder by using ANSYS software - Zhang, Kai Yuan (2015)
In this research, a steel box girder was analyzed ANSYS program with the Monte Carlo simulation direct sampling probabilistic method. The objective of this analysis is to modeling the box girder in an ANSYS FEM design, check the frame structure of box girder in force and moments, axial + bending and stress and strain graph and to determine the result based on difference graph. In addition, the structure is checked accordingly bothto Eurocode 2 and Eurocode 3. Nowadays box girder is widely used for the construction of the bridge. It is very convenient to place the electric cable or any other necessary equipment which the designer wish to go through it. A significant advantage of box girder is able to support large amounts of weight in the same length compared to the I-beam. The continuing expansion of the road network throughout the world mainly in traffic greatly improved results of extensive city population and urban growth. Span range is more for box girder-bridge as the comparison of the T shaped beam-bridge produces a relatively small number of piers with the valley width and the resulting economic. From the results of simulation, we get to know the real behaviour of the structure under the applied loads. In probabilistic analysis, we get the results of probabilistic density function plot, cumulative distribution function plot and histogram plot by 1000 times of simulation for any input and output.